Analisis Faktor Kesiapan Akademik Terkait Orientasi Motivasi Berprestasi, M-Score dan Kegiatan Non Akademik terhadap Prestasi Akademik Mahasiswa - Astri Ocvitasari; Dhanti Erma Widiasi; Marindra Firmansyah (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2020)
Background: One of the academic achievement of Medicine Faculty students of UNISMA is determined by curriculum block score. Students with curriculum block score under 68 have to take remediation. Students who take remediation indicate that they aren’t ready to attend lectures. Academic readiness was shaped by several indicators, including achievement motivation orientation, m-score and non-academic activities of students is a factor that influenced academic achievement; that is curriculum block score. This research aims to prove whether academic readiness related to achievement motivation orientation, m-score and non-academic activities affect academic readinesss.Method: This descriptive analytic research with cross-sectional approach applied sampling in students at the year of 2017, 2018 and 2019 of Medicine Faculty of UNISMA as many as 253 respondents. The data of achievement motivation orientation of the students used questionnaires of Academic Readiness Questionnaire (ARQ). The data of M-Score was the result of students’s final national examination when they were in senior high school. The data of non-academic activities of the students was related to the questionnaires made by the researcher based on the condition in the Medicine Faculty of UNISMA. To prove the relevance of academic readiness dimension and the impact on academic achievement, researcher used path analysis with SEM-PLS method.Result: Academic readiness was formed by Achievement Motivation Orientation (AMO), M-Score and Non-Academic Activities (NAA) dimension with p = 0.00 (p <0.05) and R2 AMO=0,671; R2 NAA=0,659. Academic readiness could be positively influenced by the academic achievement by p = 0.00 (p<0,05) and explained by 26.9% with R2 = 0.269.Conclusion: The academic readiness model related to achievement motivation orientation, m-score and non-academic activities affect to academic achievement is a fit or apropriate.Keywords: Academic Readiness, Achievement Motivation Orientation, M-Score, Non-Academic Activities, Academic Achievement.